Hyperarousal Symptoms in Survivors of Cardiac Arrest Are Associated With 13 Month Risk of Major Adverse Cardiovascular Events and All-Cause Mortality. Issue 6 (11th February 2020) - Presciutti, Alex; Shaffer, Jonathan; Sumner, Jennifer A; Elkind, Mitchell S V; Roh, David J; Park, Soojin; Claassen, Jan; Edmondson, Donald; Agarwal, Sachin
Abstract: Background: Key dimensions of cardiac arrest-induced posttraumatic stress disorder (PTSD) symptoms include reexperiencing, avoidance, numbing, and hyperarousal. It remains unknown which dimensions are most predictive of outcome. Purpose: To determine which dimensions of cardiac arrest-induced PTSD are predictive of clinical outcome within 13 months posthospital discharge. Methods: PTSD symptoms were assessed in survivors of cardiac arrest who were able to complete psychological screening measures at hospital discharge via the PTSD Checklist-Specific scale, which queries for 17 symptoms using five levels of severity. Responses on items for each symptom dimension of the four-factor numbing model (reexperiencing, avoidance, numbing, and hyperarousal) were converted to Z-scores and treated as continuous predictors. The combined primary endpoint was all-cause mortality (ACM) or major adverse cardiovascular events (MACE; hospitalization for myocardial infarction, unstable angina, heart failure, emergency coronary revascularization, or urgent defibrillator/pacemaker placements) within 13 months postdischarge. Four bivariate Cox proportional hazards survival models evaluated associations between individual symptom dimensions and ACM/MACE. A multivariable model then evaluated whether significant bivariate predictors remained independent predictors of the primary outcome after adjusting for age, sex, comorbidities, premorbid psychiatric diagnoses, and initial cardiac rhythm. Results: A total of 114 patients (59.6% men, 52.6% white, mean age: 54.6 ± 13 years) were included. In bivariate analyses, only hyperarousal was significantly associated with ACM/MACE. In a fully adjusted model, 1 standard deviation increase in hyperarousal symptoms corresponded to a two-times increased risk of experiencing ACM/MACE. Conclusions: Greater level of hyperarousal symptoms was associated with a higher risk of ACM/MACE within 13 months postcardiac arrest. This initial evidence should be further investigated in a larger sample. Abstract : Survivors of cardiac arrest who experienced greater hyperarousal symptoms at hospital discharge also experienced a higher risk of adverse cardiovascular events and death within 13-months post-hospital discharge.